Economic evaluation of iodine deficiency disorder control program in Sikkim: A cost-benefit analysis - Chandrakant S Pandav (Wolters Kluwer Medknow Publications, 2012)
Background: Iodine deficiency disorders (IDDs) are the most common cause of preventable brain damage globally. The strategy of prevention and control of iodine deficiency is based on iodine supplementation. Edible salt iodization and iodized oil injections are the two most commonly used vehicles for iodine supplementation. The objective of the study was to conduct a cost-benefit analysis of the two programs of iodine supplementation, i.e., iodized salt program (ISP) and iodized oil program (IOP) against no preventive program (NPP) option. Materials and Methods: The study was conducted in 1990 in the state of Sikkim in India. The costs were calculated on the assumption of universal coverage of ISP and coverage of IOP among all children aged 0-14 years and women in the age group of 15-44 years. Direct and indirect cost of ISP and direct cost of IOP was computed based on the costs of year 1991. The discount rate taken was 10% and all the costs were converted to the year 2010 using wholesale price index (WPI) data. Consequences in terms of health effects, Social/emotional effects, and resource use were included. Results: The discounted cost of ISP and IOP was Rs. 59,225,964 and Rs. 46,145,491, respectively. In ISP, 64.1% of the total cost was required for salt iodization, 17.6% for monitoring, and 18.3% for communication. In IOP, 50.9% of the costs were required for iodized oil; rest was for syringes and needles, manpower expenses, travel, and communication. Total resource saving was Rs. 95,566,220 for ISP and Rs. 92,177,548 for IOP. Incremental benefit for ISP was Rs. 36,340,256 and Rs. 46,032,057 for IOP. The cost-benefit ratio for ISP was 1.61 and 2.00 for IOP. Conclusion: IOP has a higher cost-benefit ratio for prevention of IDDs than ISP in the state of Sikkim, India.